2017
DOI: 10.1002/jcp.26053
|View full text |Cite
|
Sign up to set email alerts
|

Poly r(C) binding protein 1‐mediated regulation of microRNA expression underlies post‐sevoflurane amelioration of acute lung injury in rats

Abstract: Acute lung injury (ALI) presents a pervasive health burden due to the high morbidity and mortality associated with it. Volatile anesthetics like sevoflurane has been previously shown to have organ-protective effect, both in the context of normal physiological function in liver, and during LPS-induced ALI. Sevoflurane was shown to exert lung protective effect during LPS-induced ALI by modulating expression level of microRNAs (miRNAs), specifically miR-155. The objective of the current study was to define the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Several studies have reported the role of miRNAs as biomarkers of ALI, and their potential use as therapeutic targets for this condition [38][39][40][41]. Microarray data from various experimental models reveal that ALI induces aberrant expression of miRNAs and the potential targets for these miRNAs that are associated with many pathophysiological processes such as inflammation and apoptosis [42,43]. In the present, by using miRNA microarray analyses, we found a large set of miRNAs were significantly deregulated in injured lung tissues compared with normal group, and the expression of miR-27a was further confirmed by qRT-PCR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the role of miRNAs as biomarkers of ALI, and their potential use as therapeutic targets for this condition [38][39][40][41]. Microarray data from various experimental models reveal that ALI induces aberrant expression of miRNAs and the potential targets for these miRNAs that are associated with many pathophysiological processes such as inflammation and apoptosis [42,43]. In the present, by using miRNA microarray analyses, we found a large set of miRNAs were significantly deregulated in injured lung tissues compared with normal group, and the expression of miR-27a was further confirmed by qRT-PCR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…4a, c ). To determine if PCBP1 associates with the rat Hapln2 pre-mRNA, RIP was performed in the hippocampus of both male and female rats, using a PCBP1 antibody [ 29 , 30 ] followed by qPCR using primers surrounding the cytosine rich PCBP1 motif in Hapln2 (Fig. 4a ).…”
Section: Resultsmentioning
confidence: 99%
“…140 μl of clarified supernatant was incubated overnight at 4 °C with 5 μg of mouse monoclonal anti-PCBP1 antibody (AB_2299322, #sc137249, Santa Cruz Biotechnology), and the remaining 40 μl was used as input. PCBP1 antibody has been validated in rat tissue and used for western blot and immunoprecipitation [ 14 , 29 , 30 ]. Positive and negative controls used anti-Hur and anti-IgG antibodies respectively (#03-102 Millipore Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…Fu et al [ 91 ] reported that LPS further enhanced the upregulation of miR-155 in the prostatic tissues of mice with experimental autoimmune prostatitis. In a LPS-induced acute lung injury animal model, miR-155 expression was found to be significantly upregulated in the lungs of mice and rats, and reached a peak at 6 h of LPS stimulation [ 128 , 129 ]. Bala et al [ 130 ] also observed an increase of miR-155 levels in the livers of WT mice following LPS or alcohol treatment, which was significantly eliminated by knockout of TLR4.…”
Section: Inductive Effect Of Tlr4 Activation On Mir-155mentioning
confidence: 99%